Examination of the gamma radiation shielding properties of different clay and sand materials in the Adrar region - Sara Abbane; Mohammed Boussaid; Amine Dib Anis Sami (Open Physics)
Four samples of natural sand and clay materials from the Adrar region in southern Algeria were studied for their shielding parameters at three chosen energies in this work (0.662, 1.172,1.333 MeV). There was only a small difference between the outcomes demonstrated by Géant 4 and WinXcom. Due to the nearly equal density of the materials examined, the shielding coefficients were likewise similar. But the green clay was the best, as the value of the linear attenuation coefficient (LAC) is equal to 0.117 cm−1 at photon energy was 1.172 MeV and it required a small thickness half-value layer equal to 5.903 cm. Subsequently, sand, red clay, and white clay follow green clay in a sequential manner.